(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: At healthcare facilities, the satisfaction of patients during their medical visits heavily relies on the quality of service, including professional competence, service attitude, administrative procedures, and costs. Ensuring healthcare quality for participants of health insurance requires effective management of healthcare services, which must be carefully attended to and implemented by the health insurance management. Objective: Describe the results of managing healthcare services under health insurance at the My Tu Dist health center in 2023. Method: Cross-sectional descriptive study, interviewing 400 individuals who utilized health insurance for medical visits at the My Tu Dist health center from From May to July 2023. Results: Simple and understandable medical examination procedures (97.0%); Healthcare staff with good service spirit and friendliness (97.2%); Well-organized medication distribution process (97.9%); Transparent payment procedures (99.5%); Appropriate treatment costs (88.7%). Conclusion: Lack of highly skilled manpower; Deteriorating physical infrastructure lacking maintenance, repair, and upgrades; Insufficient modern equipment; High rate of health insurance payment refusals.